Cutibacterium acnes Phylotype I and II Strains Interact Differently With Human Skin Cells - Spittaels, Karl-Jan; Ongena, Ruben; Zouboulis, Christos C.; Crabbé, Aurélie; Coenye, Tom (Frontiers in Cellular and Infection Microbiology, 2020)
Acne vulgaris is one of the most common skin disorders and affects the pilosebaceous units. Although the exact pathogenesis of acne is still unknown, Cutibacterium acnes (formerly known as Propionibacterium acnes) is considered one of the key contributing factors. In fact, a significant association exists between C. acnes strains belonging to phylotype I and acne. However, there is still heavy debate on the exact role of C. acnes in acne and its behavior in the pilosebaceous unit, and more specifically its interactions with the human skin cells. In this study, key elements of the host-pathogen interaction were studied for a collection of C. acnes strains, belonging to phylotype I and II, including association with HaCaT keratinocytes and SZ95 sebocytes, the effect of C. acnes on keratinocyte tight junctions in a HaCaT monoculture and in an additional keratinocyte-sebocyte co-culture model, and C. acnes invasion through the keratinocyte cell layer. Our data showed association of all C. acnes strains to both skin cell lines, with a significantly higher association of type I strains compared to type II strains. Microscopic imaging and western blot analysis of the tight junction protein ZO-1, together with transepithelial electrical resistance (TEER) measurements revealed an initial induction of keratinocyte tight junctions after 24 h infection but a degradation after 48 h, demonstrating a decline in cell lining integrity during infection. Subsequently, C. acnes was able to invade after 48 h of infection, although invasion frequency was significantly higher for type II strains compared to type I strains.